Asuhan Keperawatan pada Pasien Stroke Iskemik di Rumah Sakit Dr. M. Hatta Tahun 2024 - Anita Intya Ismet; Aini Yusra; Yulvi Hardoni (CV CENDIKIA JENIUS INDONESIA, 2026)
Ischemic stroke is a brain function disorder caused by a blockage in the blood flow to the brain, leading to reduced oxygen and nutrient supply. It is a leading cause of disability and death globally, including in Indonesia. This study aims to describe the implementation of nursing care for ischemic stroke patients at Dr. Drs. M. Hatta Brain Hospital Bukittinggi in 2024. The research method used is a descriptive case study with a nursing care approach, including assessment, diagnosis, intervention, implementation, and evaluation. Data were collected through interviews, observations, and physical examinations on a patient hospitalized from March 25–29, 2024. Assessment results showed right-sided limb weakness, sleep disturbances, and fall risk. The nursing diagnoses established were impaired physical mobility, disturbed sleep patterns, and risk of falls. Nursing interventions included Range of Motion (ROM) exercises, fall prevention, and patient education. After five days of care, the patient's condition improved significantly with increased range of motion, activity tolerance, and decreased fall risk. In conclusion, systematic nursing care can enhance the quality of life for ischemic stroke patients and prevent further complications.